PENERAPAN PERBAIKAN KUALITAS PADA PROSES PRODUKSI RUBBER DI PT VALEO MENGGUNAKAN FUZZY ANALYTICAL HIERARCHY PROSES - Silalahi, Sukritno; Fauzi, Rahmat (LPPM Universitas Putera Batam, 2023)
In the era of technological and industrial development, the use of information technology developments is used in various ways including decision making within an organization or company. This research was conducted at a rubber production company in Batam City, namely PT. Valeo, the problem experienced by PT's production process is that there are many short molds in rubber production, so fuzzy logic is used regarding factors that must be maximized in the rubber production process so that the number of short molds produced is reduced. The method used is an analytical hierarchy process and professional application assistance, namely expert choice, with the aim or goal of improving the quality of rubber production at PT. Valeo, divided into 4 (four criteria) influencing factors, namely the operator does not follow the standards of chemical goods and dimensions with a criterion weight of 0.325, engine pressure with a criterion weight of 0.194, engine temperature with a criterion weight of 0.124, and chemical damage with a criterion weight of 0.356. The total criterion inconsistency value is 0.00137. The next level is the determination of solutions, there are 3 (three) solutions, namely operators with an alternative solution ranking of 0.418, machines with an alternative solution ranking of 0.182, and basic materials with an alternative solution ranking of 0.437. The results of testing using expert choice 11 software are that the solution factor that must be maximized is the basic material for making rubber to reduce shortmold with an alternative solution value of 42.5%, followed by operators 40.6% and machines 16.9%.